Real-world clinical outcomes with a next-generation left atrial appendage closure device: the FLXibility Post-Approval Study. Issue 3 (3rd February 2023) - Betts, Tim R; Grygier, Marek; Nielsen Kudsk, Jens Erik; Schmitz, Thomas; Sandri, Marcus; Casu, Gavino; Bergmann, Martin; Hildick-Smith, David; Christen, Thomas; Allocco, Dominic J; ,
Abstract: Aims: The FLXibility Post-Approval Study collected data on unselected patients implanted with a WATCHMAN FLX in a commercial clinical setting. Methods and results: Patients were implanted with a WATCHMAN FLX per local standard of care, with a subsequent first follow-up visit from 45 to 120 days post-implant and a final follow-up at 1-year post-procedure. A Clinical Event Committee adjudicated all major adverse events and TEE/CT imaging results were adjudicated by a core laboratory. Among 300 patients enrolled at 17 centres in Europe, the mean age was 74.6 ± 8.0 years, mean CHA2DS2-VASc score was 4.3 ± 1.6, and 62.1% were male. The device was successfully implanted in 99.0% (297/300) of patients. The post-implant medication regimen was DAPT for 87.3% (262/300). At first follow-up, core-lab adjudicated complete seal was 88.2% (149/169), 9.5% (16/169) had leak <3 mm, 2.4 (4/169) had leak ≥3 mm to ≤5 mm, and 0% had >5 mm leak. At 1 year, 93.3% (280/300) had final follow-up; 60.5% of patients were on a single antiplatelet medication, 21.4% were on DAPT, 5.6% were on direct oral anticoagulation, and 12.1% were not taking any antiplatelet/anticoagulation medication. Adverse event rates through 1 year were: all-cause death 10.8% (32/295); CV/unexplained death 5.1% (15/295); disabling and non-disabling stroke each 1.0% (3/295, all non-fatal); pericardial effusion requiring surgery or pericardiocentesis 1.0% (3/295); and device-related thrombus 2.4% (7/295). Conclusion: The WATCHMAN FLX device had excellent procedural success rates, high LAA seal rates, and low rates of thromboembolic events in everyday clinical practice. Graphical Abstract: Graphical Abstract